TRANSFORMASI STRUKTUR KETENAGAKERJAAN DAN PERTUMBUHAN EKONOMI SUMATERA SELATAN - Yunisvita Yunisvita (Jurnal Ekonomi Pembangunan, 2011)
The result of Assessment on "Changes of Economic and Employment Structure as well as Quality of Human Resource in South Sumatera” showed that in 2005-2010 periods economic (GNP) structure in Indonesia has been changed from S-I-A (Services-Industry- Agriculture) pattern to I-S-A pattern. Meanwhile, during the same period employment structure was remain stable, namely A-S-I pattern. The unbalanced changes between economic and employment structures were predicted to be the factors causing labor  productivity and society welfare in agricultural sector were declining. There was a quality improvement in human resource. However, the problem is government capability to create employment was not sufficient to provide job opportunity for improved human resource. Keywords: Changes, Structure, Economic, Employment, and Human Resource. .